Bile Acid Malabsorption and Cholestyramine - Khan, Adnan (Journal of Postgraduate Medical Institute, 2011)
The respnse of cholestyramine, a bile acid sequestrant was studied in 30 patients in whom conventional therapy had fialed to control their symptoms. These patients were categorized into the following four groups: Group A: Patients with crohn's disease with ileal involvement. Group B: Patients with bilialry reflux gastritis; either in association with gallstones or following chlecystomy or in patients with idiopathic biliary reflux gasttirits. Group C: Post cholecystotomy patients with diarrhoea. Group D: Irritable bowel syndrome with predominant diarrhoea.